PERSEPSI GURU PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI DAN OLAHRAGA DALAM KURIKULUM MERDEKA - Noviro, Dida; Vai, Aref; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The purpose of the author in conducting this research is to determine the Perception of Physical Education, Sports and Health Teachers on Physical Education and Sports Learning in the Independent Curriculum. This research is classified as descriptive research. This design is carried out through several procedures to determine the population, sample, create a questionnaire and distribute it to teachers and students. Then the data that has been obtained is processed using descriptive techniques. The research was conducted at Bunut District School from January 2025 to March 2025. Based on the results of the research and discussion regarding the perceptions of Physical Education, Sports and Health (PJOK) teachers on PJOK learning in the Independent Curriculum in Bunut District, it can be concluded that PJOK teachers generally have a positive perception of the implementation of the Independent Curriculum in PJOK learning. They realize the importance of curriculum flexibility in providing space for creativity and innovation in the teaching and learning process. Even so, the main challenge faced is the limited facilities and infrastructure that affect the effectiveness of the implementation of PJOK learning. Learning indicators, such as learning models, teacher competencies, and school environments, show good results, but there is a need for infrastructure improvement, teacher competency development, and further understanding of the Independent Curriculum so that its implementation can be more optimal. Overall, teachers' perceptions of the Independent Curriculum in PJOK learning are in the very good category, with an average achievement of 82.50%. Keywords: Teacher Perception, Independent Curriculum